Distance motor learning during the COVID-19 induced confinement: video feedback with a pedagogical activity improves the snatch technique in young athletes - Souissi, M. A.; Ammar, A.; Trabelsi, O.; Glenn, J. M.; Boukhris, O.; Trabelsi, K.; Bouaziz, B.; Zmijewski, P.; Souissi, H.; Chikha, A. B.; Driss, T.; Chtourou, H.; et al. (International Journal of Environmental Research and Public Health, 2021)
The purpose of the present study was to investigate which of two strategies, Video Feedback with Pedagogical Activity (VF-PA) or Video Feedback (VF), would be more beneficial for the remote error correction of the snatch weightlifting technique during the confinement period. Thirty-five school aged children with at least three months of weightlifting experience were randomized to one of three training conditions: VF-PA, VF or the Control group (CONT). Subjects underwent test sessions one week before (T0) and one day after (T1) a six-session training period and a retention test session a week later (T2). During each test session, the Kinovea version 0.8.15 software measured the kinematic parameters of the snatch performance. Following distance learning sessions (T1), the VF-PA improved various kinematic parameters (i.e., barbell horizontal displacements, maximum height, looping and symmetry) compared with T0 (p < 0.5; Cohen`s d = 0.58-1.1). Most of these improvements were maintained during the retention test (T2) (p<0.01, Cohen`s d = 1.2-1.3) when compared withT0. However, the VF group improved only twoparameters (i.e., barbell symmetry and horizontal displacement) at T1 (p < 0.05; Cohen`s d = 0.9), which were not maintained at T2. Better horizontal displacement and looping values were registered during the retention test in the VF-PA group compared with theCONT group (p < 0.05, Cohen`s d = 1.49-1.52). The present findings suggest combining video feedback with pedagogical activity during the pandemic induced online coaching or physical education to improve movement learning in school aged children.